IMPROVING COGNITIVE LEARNING OUTCOMES BY USING E-MODULES - Dyah Aniza Kismiati (Lembaga Pendidikan dan Tenaga Kependidikan (Center for Teacher Training) Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar in collaboration with Lecturer Consortium of Tarbiyah and Teacher Training, 2020)
Abstract: This study aims to determine the effect of the use of e-modules in improving student cognitive learning outcomes. This type of research is a Research and Development study with ADDIE model with a nonequivalent pretest-posttest control group design. This product was validated by experts and was also limited to 21 class XI students. The research sample is 2 classes based on purposivesampling technique, class X MIPA 5 as a control class and class X MIPA 1 as an experimental class. The instrument used: a matter of cognitive learning outcomes. Data were analyzed through Independent Sample T-Test and Normalized Gain Score (N-Gain Score). The results showed that the developed E-module had a significant effect on students' cognitive learning outcomes as evidenced by the significance value of 0,000 <α 0.05 and the category of height increase from the N-Gain Score calculation of 0.846. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan e-modul dalam meningkatkan hasil belajar kognitif siswa. Jenis penelitian ini merupakan penelitian Research and Development dengan model ADDIE dengan desain nonequivalent pretest-posttest control group. Produk ini divalidasi oleh para ahli dan juga diujicobakan secara terbatas pada 21 siswa kelas XI. Sampel penelitian yaitu 2 kelas berdasarkan teknik purposive sampling, kelas X MIPA 5  sebagai kelas kontrol dan kelas X MIPA 1 sebagai kelas eksperimen. Instrumen yang digunakan adalah soal hasil belajar kognitif. Data dianalisis melalui Independent Sample T-Test dan Normalized Gain Score (N-Gain Score). Hasil  penelitian menunjukkan bahwa E-modul yang dikembangkan berpengaruh secara signifikan terhadap hasil belajar kognitif siswa yang dibuktikan dengan nilai signifikansi 0.000 <α 0.05 dan kategori peningkatan tinggi dari hasil penghitungan N-Gain Score sebesar 0.846.